Pengaruh Service Quality, Social Media Marketing Dan Customer Engagement Terhadap Keputusan Nasabah: Pengaruh Service Quality, Social Media Marketing Dan Customer Engagement Terhadap Keputusan Nasabah - Monica Jun; Tatik Mulyati; Muhammad Imron (Universitas Merdeka Madiun, 2024)
This research aims to determine the influence of service quality, social media marketing and customer engagement partially and simultaneously on customer decisions at PT Pegadaian (Persero) Magetan Branch. This research uses a quantitative approach in associative form. The data sources used are primary data and secondary data obtained directly from respondents. The population in this research were 200 customers at PT Pegadaian (Persero) Magetan Branch and the sample size used was 133 customers. The sampling technique used probability sampling technique. Data analysis was carried out using multiple linear regression with the SPSS version 25.00 for Windows program. The research results show that the independent variable service quality has a calculated t value of 3.818, the independent social media marketing variable has a calculated t value of 2.148 and the independent variable customer engagement has a calculated t value of 1.567 where the t table value for each variable is 1.710. So, partially, 1) service quality and social media marketing influence customer decisions. 2) But customer engagement has no effect on customer decisions. 3) Simultaneously, service quality, social media marketing and customer engagement influence customer decisions. 4) Service Quality is the dominant variable in influencing customer decisions.